Molecular and morphological evidence for a new species in the genus Sirodotia (Batrachospermales, Rhodophyta) from the State of Assam, India - Rossignolo, Natalia L. [UNESP]; Yasmin, Farishta; West, John A.; Ganesan, E. K.; Necchi Junior, Orlando [UNESP] (Magnolia Press, 2020)
In India the genus Sirodotia has been documented solely on morphological data. A new species of Sirodotia (Sirodotia assamica sp. nov.) was found in two localities in the State of Assam, India. Phylogenetic relationships of the new species were inferred on the basis of DNA sequence data for the plastid rbcL gene and the barcode region of the mitochondrial COI-5P gene. Taxonomic affinities of the new species were determined by morphological analyses and a distinctive character was found for this species: spermatangia arranged in clusters. Although this character is also observed in S. huillensis, both species are genetically highly divergent (4.5-5.0% for rbcL and 9.6-10.1% for COI-5P). DNA sequences from Indian specimens formed a well-supported clade, sister to S. delicatula from Malaysia. DNA sequence divergence between S. assamica and S. delicatula varied from 2.5-2.7% for rbcL and COI-5P. Intraspecific divergence between the two sequences from India were low (0.4-0.5%). A full description and photographs of the new species are provided, as well as a comparison with morphologically similar and phylogenetically allied species reported from India and other Asian regions.
Keywords: Batrachospermales; COI-5P; freshwater Rhodophyta; India; molecular systematics; rbcL